Implementasi Media Pembelajaran Berbasis Teknologi Informasi dan Komunikasi dalam Distance Learning - Muhammad Mushfi El Iq Bali (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2019)
The rapid development of science and advances in advanced technology have implications for the rhythms of human communication. A very striking implication is that people are increasingly free and easy (easy access) in obtaining information and knowledge, including in the field of education. The global education environment is seen in several ways to provide solutions to other gaps and problems through the soaring distributed learning opportunities. Learning process activities with the help of information and communication technology take place not only applied limited by space, location or level of education such as at school or college, but can be done in many different places and involve a lot of people. Learning methods from learners that are not limited to time and place are called information and communication technology based learning. Learning media that can be used in distance learning are: computers, television, radio, internet, voice recordings, and VCD tapes.